3D Printing Technologies for Drug Delivery: A Review (International Journal of Innovative Research in Engineering & Management, 2021)
With the FDA's clearance of Spritam, the first 3D printed  tablet, precedent has been established for the use of 3D printing  in the manufacture of drug delivery systems. Complex  compositions and geometries may be prepared thanks to the  ability to accurately dispense small quantities, fine spatial  control, and layer-by-layer assembly. Because of the great  degree of flexibility and control offered by 3D printing, dosage  forms including numerous active medicinal components with  complicated and customized release profiles may be created.  This technology has a one-of-a-kind potential to prepare  customized dosages to meet the requirements of specific  patients. This study will focus on the 3D printing technologies  that are being used to fabricate drug delivery systems, as well  as the formulation and processing factors that must be taken  into account. This essay will also provide an overview of the  many dosage forms that have been created utilizing these  technologies in the past ten years.
Keywords: 3D; Drug Delivery; Painting; Printing; Technology